Trace Impurities Analysis of Aluminum Nanopowder and Its Air Combustion Product; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Kabanov D. V. Denis Viktorovich; Merkulov V. G. Viktor Georgievich; Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich (2018, 2018)
Title screen